-4x-6(-2x+15)=-10

Simple and best practice solution for -4x-6(-2x+15)=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x-6(-2x+15)=-10 equation:


Simplifying
-4x + -6(-2x + 15) = -10

Reorder the terms:
-4x + -6(15 + -2x) = -10
-4x + (15 * -6 + -2x * -6) = -10
-4x + (-90 + 12x) = -10

Reorder the terms:
-90 + -4x + 12x = -10

Combine like terms: -4x + 12x = 8x
-90 + 8x = -10

Solving
-90 + 8x = -10

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '90' to each side of the equation.
-90 + 90 + 8x = -10 + 90

Combine like terms: -90 + 90 = 0
0 + 8x = -10 + 90
8x = -10 + 90

Combine like terms: -10 + 90 = 80
8x = 80

Divide each side by '8'.
x = 10

Simplifying
x = 10

See similar equations:

| 1/2(4/3)(3.14)(2.5)^3 | | -2x-3=2x+9 | | 4(6n-7)=140 | | 3(x-1)=7+5 | | n^2+9=34 | | Y=29(3)x | | 4(6n-7)=40 | | Y=29(3) | | 2/3x12/11 | | (n-6)(n-4)= | | 2j-12=2 | | -5.7=1.9+1.9z | | 4n-3=29+8n | | 2x-52=88 | | 8x-11+15x+3x+9=180 | | -5x-4(-x-17)=76 | | y+7=7(x-2) | | -10(b+645)=-490 | | 15-1/2b= | | 4w-60=440 | | 2g-17=1 | | y-6=6(x+6) | | 7xc=-3 | | 8x-1+15x+3x+9=360 | | Z+5=5 | | 5x+7(-x-14)=-88 | | 13x-30=9 | | 10x+3+3x+24=180 | | 24x^2+-12x+-12=0 | | 22/25-7/10 | | 5/20=30/x | | 8x-1+15x+3x+9=90 |

Equations solver categories